2021
DOI: 10.3390/en15010018
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Unit Commitment Algorithms for the Italian Electricity Market

Abstract: This paper focuses on the state-of-the-art of unit commitment (UC) and economic dispatch (ED) algorithms suitable for the Italian electricity market. In view of the spread of renewable energy systems (RES), the desired UC algorithm should be able to properly consider the uncertainty affecting key input variables into the formulation of the problem, as well as the different capabilities of dispatched power plants to provide ancillary services (e.g., voltage regulation). The goal of this paper is to resume the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In this study, it is also highlighted that green project investors should give importance to the diversification of the renewable energy usage. Falvo et al [19] evaluated the Italian energy market. They also concluded that the verification of clean energy usage should be provided for the success of green energy investment projects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it is also highlighted that green project investors should give importance to the diversification of the renewable energy usage. Falvo et al [19] evaluated the Italian energy market. They also concluded that the verification of clean energy usage should be provided for the success of green energy investment projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Land use and ecological protection (Alternative 2) [19] Pollution control and waste management (Alternative 3) [17] Eco-friendly transportation activities (Alternative 4) [21] Technologies of circular manufacturing (Alternative 5) [18] Green buildings (Alternative 6) [16] For the effectiveness of the green project investments, companies can focus on energy generation and efficiency. Also, land use and ecological protection t can be considered.…”
Section: Table 9 Comparative Weighting Prioritiesmentioning
confidence: 99%
“…The goal is to minimize overall costs (C), which are given by the sum of fuel costs and startup costs, as in Equation (1). Such an economically driven objective function is vastly adopted by the UC literature.…”
Section: Objective Functionmentioning
confidence: 99%
“…For this reason, experts address the thermal unit commitment (TUC) problem from several perspectives and apply different solving techniques. Obtaining solutions that balance generation costs and computational burden is usually the goal of electrical system researchers in many countries [1][2][3]. The major challenge regarding TUC comes from the specific characteristics of power generation planning problems in general [4], which consist of two stages [5]: (i) the operation decisions (ON/OFF) of the power plants, known as unit commitment (UC), and (ii) the economic dispatch of the plants in operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the uncertainty of a new power system with a high proportion of renewable energy is significantly enhanced due to the innate nature of randomness, intermittency, and volatility of wind and photovoltaic power. Compared with the traditional power grid dominated by synchronous power generation, dispatch operators are faced with much more severe challenges of real-time power balance due to the complex and changeable characteristics of system operation [2][3][4].…”
Section: Introductionmentioning
confidence: 99%